2016
DOI: 10.1136/lupus-2015-000098
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for osteoporosis and fragility fractures in patients with systemic lupus erythematosus

Abstract: Osteoporosis (OP) and fragility fractures (FFx) are a known comorbidity in patients with systemic lupus erythematosus (SLE). This work aimed at evaluating (1) the prevalence of OP and FFx in a cohort of SLE and (2) the risk factors associated with both OP and FFx. The following data were collected from clinical charts: age, sex, menopausal status (MP), body mass index, smoking habits, disease duration, daily dose and cumulative glucocorticoids (GCs), type of organ involvement, comorbidities and medications. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 31 publications
4
48
4
3
Order By: Relevance
“…In our study the prevalence of osteoporosis in patients with CTDs (mainly SLE) was of 28% at the spine and 18% at the hip. Recently, Carli et al observed that more than 50% of SLE patients chronically treated with GCs had a reduced BMD and 28% had osteoporosis (33). In previous studies the prevalence of osteoporosis in GC treated patients with SLE ranged from 1.4 to 68% (34,35).…”
Section: N Discussion and Conclusionmentioning
confidence: 99%
“…In our study the prevalence of osteoporosis in patients with CTDs (mainly SLE) was of 28% at the spine and 18% at the hip. Recently, Carli et al observed that more than 50% of SLE patients chronically treated with GCs had a reduced BMD and 28% had osteoporosis (33). In previous studies the prevalence of osteoporosis in GC treated patients with SLE ranged from 1.4 to 68% (34,35).…”
Section: N Discussion and Conclusionmentioning
confidence: 99%
“…It is however reasonable to carefully consider these comorbidities when choosing an anti-epileptic drug (AED). For example, people with systemic autoimmune diseases are at risk for osteoporosis due to glucocorticoid use [119,120] which can be further increased by certain AEDs particularly enzyme inducing AEDs [121]. In people with MS, small-sized studies indicated that use of AEDs, especially carbamazepine, are associated with increased risk of vertigo, fatigue, cognitive slowing, and even relapse-like side-effects [122,123].…”
Section: Implications For Clinical Managementmentioning
confidence: 99%
“…Osteoporosis, by densiometry, and fragility fractures have been associated with SLE(12) and in particular with prednisone therapy(13) . This is the most commonly reported item on the American College of Rheumatology/ Systemic Lupus International Collaborating Clinics damage index (ACR/SLICC SDI)(14).…”
Section: Corticosteroid Therapy In Slementioning
confidence: 99%
“…This is the most commonly reported item on the American College of Rheumatology/ Systemic Lupus International Collaborating Clinics damage index (ACR/SLICC SDI)(14). Patients with SLE also have a significantly higher risk of vertebral fractures than controls, and the majority of these fractures occur in pre-menopausal women(13, 15, 16). Zonana-Nacach et al (17) found that cumulative corticosteroid dose was most strongly associated with osteoporotic fractures, with a 2.5-fold increased risk for each decade of prednisone at 10 mg/day or more (which persisted with adjustment for age, gender, ethnicity, and exposure to high-dose and pulse therapy).…”
Section: Corticosteroid Therapy In Slementioning
confidence: 99%